Hubungan Antara Imbalan Moneter dan Kinerja Individual dengan Level Pekerjaan Karyawan dan Strategi Organisasi Sebagai Variabel Pemoderasi - LISIA APRIANI (The Indonesian Journal of Accounting Research, 2013)
The relationship between reward and performance has been the subject of much discussion in reward research. Because of prior studies didn’t give conclusive results, so it is important to examine level of employee’s position and organizational strategy in the relationships between monetary reward and individual performance.This study examines the effect of monetary reward on individual performance by examining level of employee’s position and organizational strategy as moderating variables. Mailed questionnaires were distributed to 305 employees in big companies in Indonesia. The response rate  of this research is 27,87%. Four categories of research variables are discussed and analyzed: monetary reward, level of employee’s position in organization, total  quality management based strategy, and individual performance.The results indicated that statistically, the total quality management based strategy plays direct role in the relationships between monetary reward and individual performance. In other word the greater monetary reward, spurred by increasing total quality management based strategy leads to direct influence on individual performance.